The nth term of an arithmetic sequence can be written as a + (n - 1)*d, where a is the first term and d is the common difference.

We have a2-a6+a4=-7

=> a + d - a - 5d + a + 3d = -7

=> a - d = -7

=> d = a + 7

a8 - a7 = 2*a4

=> a + 7d - a - 6d = 2*(a + 3d)

=> d = 2a + 6d

=> 2a + 5d = 0

Now substitute d = a + 7 in 2a + 5d = 0

=> 2a + 5(a + 7) = 0

=> 2a + 5a + 35 = 0

=> 7a + 35 = 0

=> a = -35/7

=> a = -5

d = a + 7 = -5 + 7 = 2

**The first term is -5 and the common difference is 2**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now